2020
DOI: 10.1101/2020.10.12.335919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Within-patient genetic diversity of SARS-CoV-2

Abstract: SARS-CoV-2, the virus responsible for the current COVID-19 pandemic, is evolving into different genetic variants by accumulating mutations as it spreads globally. In addition to this diversity of consensus genomes across patients, RNA viruses can also display genetic diversity within individual hosts, and co-existing viral variants may affect disease progression and the success of medical interventions. To systematically examine the intra-patient genetic diversity of SARS-CoV-2, we processed a large cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 59 publications
3
24
0
4
Order By: Relevance
“…In a similar way as selection is expected to decrease the frequency of deleterious SARS-CoV-2 alleles at the human population level, the same is true at the within-host levels, as selection is expected to act on within-host deleterious mutations and often prevent them from reaching high frequency and transmit further on. While within-patient genetic diversity data can indeed be very informative of the SARS-CoV-2 evolutionary patterns [ 13 , 14 , 45 ], it is important to consider that such data is also more prone to sequencing, read processing, and RNA degradation issues. These issues cause some errors in consensus sequences [ 23 , 22 ] but they are expected to be even more problematic at the level of detected within-host variation.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way as selection is expected to decrease the frequency of deleterious SARS-CoV-2 alleles at the human population level, the same is true at the within-host levels, as selection is expected to act on within-host deleterious mutations and often prevent them from reaching high frequency and transmit further on. While within-patient genetic diversity data can indeed be very informative of the SARS-CoV-2 evolutionary patterns [ 13 , 14 , 45 ], it is important to consider that such data is also more prone to sequencing, read processing, and RNA degradation issues. These issues cause some errors in consensus sequences [ 23 , 22 ] but they are expected to be even more problematic at the level of detected within-host variation.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that patients with severe COVID-19 symptoms present a more important intra-host diversity than patients with mild symptoms [ 70 ]. Furthermore, Kuipers et al established that age is significantly associated with intra-host viral genetic diversity [ 71 ]. The identification of these factors inducing new diversity is worth exploring in an in-depth analysis of existing genomic data integrated with extensive epidemiological and clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…The early evolutionary events that shaped the epistatic network conceivably laid the foundation for the diversification of the virus relevant to virulence, immune evasion, and transmission. Recent analysis of within-patient genetic diversity has shown that the most common mutations are highly diverse within individuals (37) . Such diversity could either result from multiple infections, or otherwise, could present evidence of an even greater role of positive selection affecting a larger number of sites than inferred from our tree (Fig.…”
Section: Mainmentioning
confidence: 99%